Importance of cadmium speciation in nitrification inhibition - SEMERCİ, NESLİHAN (ELSEVIER, 2007)
In this study, the influence of Cd speciation on nitrification inhibition was investigated in batch suspended growth activated sludge systems which contain biomass enriched in terms of nitrifiers. For this purpose, parallel measurements of specific oxygen uptake rates (SOUR), ammonium utilization rates (q(NH4)-N) and Cd uptake were carried out. Cd speciation was adjusted with a strong complexing agent, ethylenediaminetetraacetic acid (EDTA). Free and biosorbed Cd concentrations were theoretically determined by using the MINEQL+ program and the Cd adsorption constant, whereas labile Cd was determined by voltammetric measurements. The presence of EDTA decreased nitrification inhibition by lowering the available Cd species and by preventing biosorption of Cd. Almost complete recovery from inhibition was attained by EDTA addition to nitrifying bacteria which were inhibited by Cd for a certain time. These results suggested that the sites sensitive to Cd were rather located on the surface of bacterial cell than inside. Nitrification inhibition depended on equilibrium concentrations of free (Cd2+), labile (Cd-volt) and biosorbed Cd (Cd-volt) and did not correlate with the total Cd. The measurement of labile metal by voltammetry in inhibition studies is a promising approach since it is easy to apply in practice. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: cadmium; inhibition; nitrification; speciation; voltammetry; activated sludge; biosorption; FREE-ION ACTIVITY; HEAVY-METALS; BIOAVAILABILITY; NICKEL(II); COMPLEXES